An emerging role for microRNA in the regulation of endothelin-1 - Jacobs, Mollie E.; Wingo, Charles S.; Cain, Brian D. (Frontiers in Physiology, 2013)
Endothelin-1 (ET-1) is a peptide signaling molecule serving diverse functions in many different tissues such as the vasculature and the kidney. The primary mechanism thought to control ET-1 bioavailability is the rate of transcription from the ET-1 gene (EDN1), but recent research suggests that EDN1 expression is attenuated by microRNA (miRNA) –mediated regulation. The action of specific miRNAs on EDN1 mRNA appears to vary greatly in a tissue specific manner. This review provides a summary of our current understanding of miRNA-EDN1 interaction.